Death in custody : inquests, family participation and state accountability - Easton, Jo (Emerald Publishing Limited, 2020)
Death in Custody considers the participation of bereaved families in an inquest following a death in custody. It looks at the legal frameworks governing participation, as well as relevant theories of justice, participation, procedural fairness and grief theory. Interviews were carried out with people with personal experience of complex inquests, including bereaved family members. Participation can provide families with redress and allow them to represent the deceased, as well as being an important part of their grief process. It also helps to ensure a fair process, which has a positive impact on accountability and legitimacy. Family participation improves accountability by maximising the chance of achieving the right outcome via scrutiny, therefore identifying failures. Families also brings balance to the process, provide vital information about the deceased as well as helping to ensure that lessons are learned that will prevent future deaths. Death in Custody shows that procedural justice theory is relevant for participation in processes investigating human rights violations. It includes key recommendations on how to ensure participation can be fair and effective.